VALSARTAN TO ATTENUATE RENAL DAMAGE IN UNILATERAL URETERAL OBSTRUCTION - Jusuf, Samycha; Alvarino, Alvarino (Indonesian Urological Association, 2014)
Objective: This experimental study aims to observe the effect of valsartan to attenuate renal damage in unilateral ureteral obstruction. Material & method: Experimental study was performed using 30 wistar rats with unilateral ureteral obstruction achieved by ligation of the left ureter. Rats were divided into two groups, no treatment group and valsartan group. At the 14th day, evaluation was performed to compare interstitial fibrosis, hydropic degeneration, and tubular atrophy between the two groups using haematoxylin-eosin staining. Only rats surviving until at least the 7th day are included in the study. Results: From thirteen wistar rats in no treatment group, there were two with moderate interstitial fibrosis and eleven with mild interstitial fibrosis while all rats in valsartan group had mild interstitial fibrosis (p > 0.05). There is no significant difference on hydropic degeneration between no treatment and valsartan group (31.46 vs 33.67; p > 0.05). There is also no significant difference in tubular atrophy between the two groups (61.78 vs 62.07; p > 0.05). Conclusion: Valsartan therapy in antihypertensive dosage has no significant effect in to attenuate interstitial fibrosis, hydropic degeneration, and tubular atrophy in unilateral ureteral obstruction in wistar rats. Keywords: Unilateral ureteral obstruction, valsartan, interstitial fibrosis.